Effect of inulin as thickener agent and purple sweet potato extract on the characteristics of Aloe vera jam : Pengaruh konsentrasi pengental inulin dan ekstrak ubi jalar ungu terhadap karakteristik selai lidah buaya (Aloe vera) - Wahyu Sasono; Merkuria Karyantina; Nanik Suhartatik (Fakultas Sains dan Teknologi Unisri, 2025)
Jam is a paste-shaped food usually made from fruit which is quite popular from children to teenagers. Aloe vera is one of the 10 best-selling plant species in the world which was developed as a raw material in the pharmaceutical and food industries, especially in countries on the European continent. Inulin is a dietary fiber contained in various types of vegetables and fruits that are beneficial for digestive health. Purple sweet potato is used in the addition of jam because purple sweet potato contains vitamin A, B vitamins and antioxidants. The purpose of this study was to determine the concentration of inulin thickener and purple sweet potato extract with high antioxidant activity, and to determine the characteristics of the panelists' preference to jam. This study used a completely randomized design with the first factor being variations in the concentration of inulin as thickener 1, 2, and 3 g. The second factor was the addition of purple sweet potato extract (40, 50, and 60%). The results of this study indicated that the jam formulation with high antioxidant activity on variations in the concentration of 1 g of inulin thickener with the addition of 60% purple sweet potato extract. The jam formulation that was preferred by the panelists was found in variations in the concentration of 2 g of inulin with the addition of 40% purple sweet potato extract which had an overall value of 3,40 (neutral). Higher purple sweet potato extract, the higher the antioxidant activity of the jam. Purple sweet potato extract can be used as a source of antioxidants in jam making.